A Comprehensive Study on Biochar Production, Bibliometric Analysis, and Collaborative Teaching Practicum for Sustainable Development Goals (SDGs) in Islamic Schools - Ramdhani, Muhammad Rendi; Kholik, Abdul; Fauziah, Siti Pupu; Roestamy, Martin; Suherman, Irman; Nandiyanto, Asep Bayu Dani (Jurnal Pendidikan Islam, 2023)
This research endeavors to assess the impact of additional practicum sessions and experimental demonstrations through video presentations on students' comprehension in an Islamic boarding school. The study focuses on enhancing students' understanding of the biochar concept, particularly its role as an adsorbent, aligning with contemporary issues related to the Sustainable Development Goals (SDGs) and environmental problem-solving. To substantiate the research rationale, a concise literature review and bibliometric analysis were incorporated. The experiment involved comparing two classes – the experimental class, which received additional practicum and experimental demonstrations using videos, and the conventional class as the control group. The study included 45 students in Class XI of an Islamic boarding school. Learning outcomes were assessed through pre-test and post-test scores, as well as N-Gain calculations. The hypothesis was tested using the Paired Sample T-test. The practical aspect of the experiment involved carbonizing the skin of jengkol fruit to produce carbon, which was then utilized for adsorbing curcumin. The adsorption phenomena were observed and analyzed.The research findings demonstrated that the experimental demonstration method, particularly when complemented with video presentations, was more effective than conventional methods. This was evident from the N-Gain value of the experimental class and the results of statistical tests. The experimental demonstration method using videos is anticipated to enhance knowledge, provide a more authentic understanding and experience, and yield superior learning outcomes. These findings contribute valuable insights for future research on experimental demonstrations, emphasizing their potential to enhance the overall quality of student learning.